4D printing reversible actuator with strain self-sensing function via structural design. (15th April 2021) - Wang, Yanan; Li, Xiang
Abstract: The integration of sense functionality with the four-dimensional (4D) printed reversible actuator that fully eliminates human interference can further promote the application of 4D printing in intelligent devices and humanoid machines. In this study, a promising strategy is proposed to manufacture a reversible actuator capable of strain self-sensing via structural design and a combination of bilayer composites. A wiggle structure with oblique sides that changes the contact resistance during longitudinal deformation is designed to integrate actuators with sensing capabilities. The shape-memory effect of the conductive graphene polylactic acid (GPLA) in the bilayer structure enables voltage-controlled reversible deformation capability in the actuator, and the deformation direction was controlled by the wiggle structure. Owing to the controllable deformation, rapid response, sensitive sensing, and strong feedback signal, 4D printed low-cost sensor-reversible actuators can be used to build a feedback system for intelligent mechanical claws that can perceive the shape of objects. The design principles in this work can be referred to for designing 4D printed intelligent actuators with various functionalities that meet the requirements for different applications.